Prophylaxis of murine candidiasis via application of liposome-encapsulated amphotericin B and a muramyl dipeptide analog, alone and in combination. - Mehta, R T (1985)
The present study was conducted to examine the effect of a lipophilic analog of muramyl dipeptide, 6-O-stearoyl-N-acetylmuramyl-L-alpha-aminobutyryl-D-isoglutamine (6-O-S-Abu-MDP), a macrophage activator, on the prophylactic activity of liposomal amphotericin B (L-AmpB) against disseminated candidiasis in mice. Multilamellar vesicles containing AmpB and (6-O-S-Abu)-MDP were prepared by using dimyristoyl phosphatidylcholine and dimyristoyl phosphatidylglycerol (7:3 molar ratio). Hale-Stoner mice (6 to 8 weeks old) were injected with 7 X 10(5) CFU of Candida albicans 336 isolated from a patient. Groups of mice were injected intravenously with different doses of L-AmpB and L-(6-O-S-Abu)-MDP, individually or in combination, 2 days before challenge with C. albicans. The mice were injected with a fixed dose of L-AmpB (1.2 mg/kg in 400 mg of lipid per kg) and various doses of L-(6-O-S-Abu)-MDP (0.6, 1.2, 2, and 4 mg/kg in 400 mg of lipid per kg) or vice versa. Other control groups included untreated mice and those receiving empty liposomes (400 mg of lipid per kg), free AmpB (0.6 mg/kg), or free (6-O-S-Abu)-MDP (4 mg/kg). The mice receiving L-AmpB (1.2 mg/kg) plus L-(6-O-S-Abu)-MDP (0.6 to 4.0 mg/kg) survived up to 25 to 30 days as compared with those injected with L-AmpB alone (15 days) or with L-(6-O-S-Abu)-MDP alone (10 to 15 days). All the mice in other control groups died within 7 to 11 days. The kidney cultures of the mice that received L-AmpB (4 mg/kg) plus L-(6-O-S-Abu)-MDP (1.2 mg/kg) were free of C. albicans infection, unlike those injected with L-AmpB. Variance analysis of these findings indicates a synergistic activity between L-AmpB and L-(6-O-S-Abu)-MDP in the prophylaxis of candidiasis.